2020
DOI: 10.1002/ese3.651
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and longevity of solar photovoltaic modules—An analysis of recent field studies in Ghana

Abstract: Solar photovoltaic (PV) technology has attracted an enormous amount of attention and investment in recent years—translating to record deployment levels. This is due to in part to its potential role as a cleaner energy source in the emissions‐constrained development agenda that is currently being pursued at both global and national levels. Solar PV has also been propelled to the forefront of today's menu of technological options by virtue of its attributes such as scalability, fast deployment lead times, and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…44,45 Lots of experimental, modeling, and theoretical investigations have been done to assess the behavior of solar systems. [46][47][48][49][50][51][52] Various variables like solar radiation, the initial temperature of the coolant, geometry, material and incline angle of system, coating layers, and different kinds of working fluids are most discussed.…”
mentioning
confidence: 99%
“…44,45 Lots of experimental, modeling, and theoretical investigations have been done to assess the behavior of solar systems. [46][47][48][49][50][51][52] Various variables like solar radiation, the initial temperature of the coolant, geometry, material and incline angle of system, coating layers, and different kinds of working fluids are most discussed.…”
mentioning
confidence: 99%
“…The selection of an optimal tilt angle and orientation for a solar PV module must be determined on a case-by-case basis [15], taking into account the local site conditions [16] and cost factors to ensure that the most effective and efficient selection is made for a given installation [17]. Generally, the selection of an optimal tilt angle and orientation for a solar PV module is an important consideration when installing one, as it can have a direct effect on the efficiency [18] and lifespan of the module [19]. Therefore, it is important to carefully weigh the potential costs associated with increasing the tilt angle of a solar PV module against the benefit of increased efficiency when making the decision [20].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that careful attention must be paid to the cleanliness of PV modules and their tilt angle in order to maximize photovoltaic efficiency and energy production and to receive the most benefit from a solar photovoltaic system over the long run. Most studies revealed that soiling impacts negatively on the radiation and energy performance of PV systems and that it can be as high as 25% [18], which is substantial, and it could be argued that this underlines the importance of regular cleaning and maintenance of PV modules [25], whereas an optimal tilt angle enhances PV performance by increasing the amount of solar radiation absorbed and therefore increasing the efficiency of a PV system significantly [26].…”
Section: Introductionmentioning
confidence: 99%
“…With the increasingly prominent environmental and energy problems, the proportion of renewable energy represented by PV is increasing year by year. 1 However, the randomness and uncertainty of PV power generation reduce the reliability of PV power generation and the stability of power grid. 2 Therefore, it is particularly important to accurately predict PV power generation and take certain measures to deal with its randomness and uncertainty, which can provide support for the development of PV industry.…”
Section: Introductionmentioning
confidence: 99%